PENINGKATAN AKTIVITAS BELAJAR SISWA KELAS XI PADA MATERI ASAM DAN BASA MELALUI STUDI KASUS SECARA BERKELOMPOK DI SMAN 1 LUHAK NAN DUO - Handayani, Mila (Jurnal Manajemen Pendidikan, 2018)
During teaching, it was found that many students were less active in learning so that learning activities decreased, teachers were no longer facilitators, teachers were more likely to teach by using the lecture method so students only acted as passive learning agents. In accordance with the problems and objectives of the study, this type of research is Class Action Research (CAR). Classroom Action Research is a form of research that is carried out directly by the teacher in the practice of learning, where the teacher (researcher) conducts certain actions based on important problems in the field that must be addressed immediately. With students in groups can make students more active in the learning process. By providing reinforcement to students who answer or who want to express opinions make students more active Giving tests at the end of learning can increase students' attention in learning